Investigation of Energy and Cost Potential in an Office Building Using IoT Lighting System - Ayub, Muhammad Hizami; Mohd.Sari, Kamarul Aini; Tong, Benedict (Progress in Engineering Application and Technology, 2025)
This study analyses the potential energy and cost savings through the implementation of an Internet of Things (IoT)-based lighting system in an office building, with a specific focus on Sunway Geo Tower, Subang Jaya, Malaysia. The research aims to analyses lighting energy consumption patterns before and after the implementation of IoT technology, assess the potential energy reduction, and calculate the return on investment (ROI). Data was collected through site inspections, interviews, electricity bills and data obtained from the building’s facilities management system, CMMS (Easy10). Additional simulations were also conducted to estimate energy consumption if the IoT system was not used. The IoT-based lighting system uses motion sensors and two-stage lighting modes of Day Mode (100%) and Night Mode (30%) which are automatically controlled based on occupancy and operating hours. The results of the study show a 30% energy reduction, from 4,948.92 kWh to 3,464.24 kWh per month. These energy savings also result in significant cost savings and a favorable return on investment, thus proving the effectiveness of investing in smart lighting technology. The findings of this study are also in line with the MS1525:2019 guidelines and the Green Building Index (GBI) which support the use of smart lighting controls to optimize energy consumption in commercial buildings. Overall, this study proves that IoT-based lighting systems are a practical and capable solution to improve energy efficiency, reduce operating costs and support sustainability goals. The results of this study are very useful for facility managers, building developers, and policymakers in empowering smart building practices in Malaysia